Cars and space consumption: Rethinking the regulation of urban mobility - Yves Crozet (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper discusses the importance of reducing the space consumption of car traffic as opposed to simply reducing individuals' travel time. It highlights the role of app-based mobility services in reducing urban congestion from a spatial perspective and the importance of shifting the focus from mobility to accessibility as a way of reducing excessive traffic, meeting sustainability objectives and improving livability.
Keywords: 330; Stadtverkehr; Nachhaltige Mobilität; Räumliche Wirkung; Transportzeit; Lebensqualität